The birds of America - Audubon, John James, 1785-1851; Bowen, John T., approximately 1801-1856?; Dorsey, E. G.; Chevalier, J. B.; Audubon, John James, 1785-1851; Bowen, John T., approximately 1801-1856?; Audubon, John Woodhouse, 1812-1862; G. & W. Endicott (Firm) (New York, J.J. Audubon; Philadelphia, J.B. Chevalier, 1840)
This edition has 65 new images, making a total of 500. The original configurations were altered so that there is only one species per plate. The text is a revision of the Ornithological Biography, rearranged according to Audubon's Synopsis of the Birds of North America (1839).
Contains bibliographies.
Tyler, R. Audubon's great national work
Sabin, J. Dictionary of books relating to America from its discovery to the present time
Herrick, F.H. "Audubon's bibliography." In Auk, volume 36, no. 3(1919): 372-380
Nissen, C. Illustrierten Vogelbücher
Herrick, F.H. "Audubon's bibliography." (Auk, 36:3 (July 1919): 372-380)
Keywords: Birds -- North America -- Pictorial works; Birds -- North America; Pictorial works; Lithographs; Gilt edges (Binding); Fillet tools (Binding); Leather bindings (Binding); Subscription publications; Intaglio prints; Lithographs; Books issued in fascicles (Publishing); Subscription lists (Publishing)